KAJIAN INTERTEKSTUAL CERITA RAKYAT DENGAN BALADA RAKYAT - Amelia, Rizca; Elmustian, Elmustian; Syafrial, Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is titled Intertextual Study of Folk Stories with Balada Rakyat. The background of this research is that researchers want to see how the intrinsic elements of folklore are compared as hypary text with ballad poetry as a new form of literary work. The aim of this study is to find out the comparison of intrinsic elements of folktales with ballad seal. This research is a descriptive qualitative research that describes and describes the results of the research carried out. According to research, there are five ballad dens with fewer stanzas than the number of paragraphs of folklore. While in the other three ballads poems the number of verses of ballad poetry is greater than the number of paragraphs of folklore. In numbers, there are four ballad dens that some folklore figures do not bring up, while the other four ballad dens maintain the existence of folklore figures. The background of folklore and ballad poetry has some differences, including the reduction of the background. While there is no difference in characterizations, themes and perspectives between folktales and ballad poems.Key Words : Comparison, intertextual, folklore, ballad poetry, intrinsic elements